FEATURES OF COORDINATION OF INTERESTS OF THE STATE AND TAXPAYERS AT THE SUBNATIONAL LEVEL - V. Molodykh; T. Kulakovskaya (Вестник Северо-Кавказского федерального университета)
The article assesses the possibility of coordinating the interests of the state and taxpayers, taking into account the subnational specifics of the budget and tax systems based on clustering of the subjects of the Russian Federation by the level of tax discipline and tax potential. The results showed a high level of differentiation of Russian regions and the presence of a number of restrictions in the use of tax control procedures in order to increase the level of tax discipline. It is advisable to more actively use the methodology of behavioral Economics and economic psychology to optimize control activities based on appropriate models, which will increase the level of voluntary compliance with legislation.